ZnO-Cu2O core-shell nanowires as stable and fast response photodetectors. (September 2018) - Ghamgosar, Pedram; Rigoni, Federica; You, Shujie; Dobryden, Illia; Kohan, Mojtaba Gilzad; Pellegrino, Anna Lucia; Concina, Isabella; Almqvist, Nils; Malandrino, Graziella; Vomiero, Alberto
Abstract: In this work, we present all-oxide p-n junction core-shell nanowires (NWs) as fast and stable self-powered photodetectors. Hydrothermally grown n-type ZnO NWs were conformal covered by different thicknesses (up to 420 nm) of p-type copper oxide layers through metalorganic chemical vapor deposition (MOCVD). The ZnO NWs exhibit a single crystalline Wurtzite structure, preferentially grown along the [002] direction, and energy gap Eg = 3.24 eV. Depending on the deposition temperature, the copper oxide shell exhibits either a crystalline cubic structure of pure Cu2 O phase (MOCVD at 250 °C) or a cubic structure of Cu2 O with the presence of CuO phase impurities (MOCVD at 300 °C), with energy gap of 2.48 eV. The electrical measurements indicate the formation of a p-n junction after the deposition of the copper oxide layer. The core-shell photodetectors present a photoresponsivity at 0 V bias voltage up to 7.7 µA/W and time response ≤ 0.09 s, the fastest ever reported for oxide photodetectors in the visible range, and among the fastest including photodetectors with response limited to the UV region. The bare ZnO NWs have slow photoresponsivity, without recovery after the end of photo-stimulation. The fast time response for the core-shell structures is due to the presence of the p-n junctions, which enables fast exciton separation and charge extraction. Additionally, the suitable electronic structure of the ZnO-Cu2 O heterojunction enables self-powering of the device at 0 V bias voltage. These results represent a significant advancement in the development of low-cost, high efficiency and self-powered photodetectors, highlighting the need of fine tuning the morphology, composition and electronic properties of p-n junctions to maximize device performances. Graphical abstract: fx1 Highlights: High performance self-powered visible light photodetectors based on metal oxides are developed. P-n core-shell ZnO-Cu2 O nanowire junctions are produced by cheap and easy routine processes (hydrothermal + CVD). Strong/fast photo-response to 1 sun radiation (response time<0.09 s, the fastest so far for visible oxide photodetectors). Strong light absorption and efficient charge transport/collection determine the outstanding functionalities. Combined optical spectroscopies and AC impedance spectroscopy give full account of both light management and electrical features.